Evaluating the potential merger of two internal medicine residency programs: process and recommendations - Richard Alweis; Christina Goodermote; Robert Mayo (Greater Baltimore Medical Center, 2019)
Background: Economic forces have led to significant consolidation within the health-care sector, but the effects of hospital mergers on graduate medical education programs are not well studied. Academic leaders may be expected to operationalize an institutional merger through educational program consolidation. Through a case study of our potential GME program consolidation, the authors present a helpful model for assessing the practicality of a program consolidation and share lessons learned. Methods: A novel exploratory process assessed the viability of four levels of integration for two internal medicine programs within a merged health system. Focused interviews with outside organizations, literature review, SWOT analysis by stakeholders, and a semi-quantitative scoring system resulted in the final recommendation to health system administration. Results: The two internal medicine programs will pursue educational and administrative synergies but will not merge. Discussion: Common challenges facing GME leadership in assessing the viability of a merger include: different organizational culture, mistrust of intentions, lack of a shared vision, lack of communication, and managing the pace of change to prevent erosion of the learning environment. Overcoming these challenges is best accomplished by establishing shared values, recognizing synergies and estimating organizational compatibility. Maximizing faculty and resident interactions while performing combined QI projects, research, or didactics can build trust over time and change the cultural norm. Early successes are vital to the process. Finally, even if residency programs do not merge, they should have common salaries and benefits so that disparities do not engender further distrust.